Methods of Strengthening Economic Management Teaching in Party School in New Era - Liu, Jinlan (Journal of Theory and Practice of Social Science, 2023)
In the process of the current social and economic development, everyone and the economy have inseparable links, Party and government cadres at all levels are the main object of party school training and education, strengthen the economic management related cognition, improve the management level is its eternal subject. This paper discusses the importance of strengthening the teaching of economic management in Party schools, analyzes the current shortcomings of the teaching of economic management in Party schools, and puts forward measures to solve the problems in order to improve the teaching quality, in order to promote our social and economic development to lay the foundation.